THE IMAGE OF WOMEN FIGURES IN FOLKLORE OF KUDUS KULON’S TOPONYMS: A LINGUISTICS ANTHROPOLOGY STUDY - Muthia, Ratna; Syukur, Fatah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2019)
This study aims to explore the image of women figures in folklore relating to the naming of a place (toponym) in the Kudus Kulon area. This study was carried out with a linguistic anthropology approach, which focuses on language as a set of symbolic resources that enter the constitution or social and individual representations in the real world. The results of this study are as follows: 1) the origin of the toponym, i.e. the name and the activity of the women figures; 2) the role of women figures, consisting of the main and side characters; 3) the relation between female and male figures in toponym can be divided into two: (a) women figures representing the husband and (b) women figures representing themselves; 4) opportunities for women figures, including opportunities to solve problems, opportunities to move according to their interests, and opportunities to participate in public roles; 5) influences of women figures, including influences on spirituality, influences on economic activities, and influences on culture.